Jogos ficcionais em Silviano Santiago - Meneses, Luís Matheus Brito (2023)
This research shows how coalition and collision among dialectic correlatives — autobiography and biography; writing and reading; image and word; life and death — in the fictional work of Silviano Santiago, especially in Mil rosas roubadas: romance (2014), produce a fictional game — in the case of our main object, a game that captures the real through what is "unreal" (LOPES, 2019). In other words, through the transience of the real, which is, we believe, a way for the narrator of Mil rosas roubadas to construct a ―historical fact‖ (BENJAMIN, 1985) on own terms — a historical fact based on inventions and juxtapositions. This research is thus a way to identify the superposition of intermediate layers (BARTHES, 2009) in Santiago‘s fiction, which relies, among other things, on literary hybridity, the use of heterogeneous images and an essayistic tone. To examine these elements, we use critical and theoretical works by authors such as Georges Didi-Huberman (1998; 2011; 2013), Michel Foucault (1988; 1999; 2004; 2014), Roland Barthes (1972; 1979; 1981; 1984; 2004; 2015), Silvina Rodrigues Lopes (2019; 2021) e Walter Benjamin (1985; 2013; 2017), for example. At the same time, we mirror the fictional work in the critical work of Silviano Santiago to identify common points of view between one another and, finally, shuffle them